PENGARUH KEBIJAKAN MONETER TERHADAP HUBUNGAN MODEL TIGA FAKTOR DENGAN RETURN SAHAM - Imronudin, Imronudin (Benefit, 2005)
This research is intended to know how the effect of monetary policy (as moderating variable)toward the relationship between three factors model and stock return. The analysis in this research usedpooled regressions. Data used in this regression analysis are return, beta, size, and book-to-marketequity of monthly portfolio. Data of stock of enterprise was taken from Indonesian Capital MarketDirectory (ICMD) from 1995 until 2002. The result of research shows that before we intakemonetary policy, three factors model could not explain stock return variation in cross section data. Threefactors model along with monetary policy (as moderating variable) add explaining in stock returnvariation in cross section data, but variable of Book-to-Market Equity individually was not significantin explaining stock return variation. Then we exclude this variable of book-to-market equity to look atis three factors model can explain stock return variation without this variable? The evidence shows that the result was not different and even better than before. This is can be seen from value of adjusted Rsquared that increasingly better, namely from 0.036550 to 0.039196.